DETERMINAN AKUNTABILITAS KEUANGAN DENGAN KUALITAS INFORMASI LAPORAN KEUANGAN SEBAGAI VARIABEL INTERVENING PADA BADAN KEUANGAN DAERAH KOTA DEPOK - Nur Fitri Dewi (JAMER : Jurnal Akuntansi Merdeka, 2023)
This paper aims to study how internal control system and human resource competence affect the information quality of local government financial statement and how its impact on financial accountability. The data collection method was a questionnaire distributed to 50 samples of the Badan Keuangan Daerah, Kota Depok. The collected data was processed using SPSS 27.00 with t test and Path Analysis. The research results show that the internal control system and human resource competency have a positive effect on the local government financial statement. The internal control system and human resource competency also have a positive effect on financial accountability, both directly and indirectly, mediated by the quality of local government financial report information. In addition, the quality of local government financial report information has a direct and positive effect on financial accountability. The results of this research can be useful for the government as input and consideration in determining policies, especially regarding improving the quality of information on government financial reports and financial accountability.